TARAS SHEVCHENKO’S ANTICIPATING IDEAS - Голянич, М. Ю. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The article deals with the main T.H. Shevchenko’s ideas concering the future man, Ukraine, human communities and separate spheres of social life.